COPD AWARENESS SURVEY: DO BELGIAN PULMONARY PHYSICIANS COMPLY WITH THE GOLD GUIDELINES 2010? - Decramer, M; Brusselle, G; Buffels, J; Corhay, JL; De Backer, W; Degryse, JM; Janssens, W; Marchand, E; Van den Brande, P; Vincken, W; Gayan-Ramirez, G; Van Craenendonck, V; et al. (Acta clinica belgica (English ed. Online), 2013)
Chronic Obstructive Pulmonary Disease (COPD) is underestimated, underdiagnosed and often undertreated in the general population. A survey of 17 structured questions, delivered to all Belgian pulmonary physicians (PPs) (116 responses), evaluated diagnosis and treatment strategies in accordance with the Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines 2010 and assessed opinions about the importance of diurnal variation of COPD symptoms. All COPD diagnoses (37% new cases) were spirometry confirmed. Main diagnostic parameters were symptoms (99%), external risk factors (99%), clinical examination (97%), exacerbations (96%) and patient mobility (96%). FEV 1 (forced expiratory volume in 1s) (97%) or FEV 1 /FVC (ratio of FEV 1 to forced vital capacity) (93%) were used most to assess diagnosis and severity. The 3 most important therapeutic objectives were symptom relief, preventing exacerbations, and improving quality of life; if these were not reached, the preferred strategy (60% of PPs) was adding another medication. Treatment strategies varied with COPD stage: short-acting β2-agonists (90%) and short-acting anti-cholinergics (59%) were used for GOLD I disease, whereas for higher stages long-acting β2-agonists (36-48%) and long-acting anti-cholinergics (79%) were given with inhaled corticosteroids (21-67%). Symptoms were perceived to vary throughout the day, affecting quality of life (97%) and mobility (89%). In particular, respiratory symptoms were more severe in the morning (51-92%), leading PPs to adapt treatment (69%). This survey demonstrated that management of COPD by PPs in Belgium is generally in line with the GOLD guidelines 2010 and that they perceive morning symptoms as being frequent and having an impact on patient's life.